Correlation of Leukocyte Esterase Positivity Levels Against the Results of Several Examination Parameters Laboratory Urinary Tract Infection in Patients at Mataram City Regional Hospital - I Made Wahyu Waisnawa; Ida Bagus Rai Wiadnya; Thomas Tandi Manu; Agrijanti Agrijanti (Jurnal Analis Medika Biosains (JAMBS), 2023)
Background : Urinary tract infection (UTI) is caused by the multiplication of bacteria in the urinary tract. The standard proving procedures for UTI are urine culture examination and urine dipstick examination (leukocyte esterase and nitrite). Objective : This study aims to measure leukocyte and nitrite values, calculate the total number of bacteria, identify Gram type, species and antibiotic sensitivity and analyze the correlation of leukocyte esterase positivity to the results of several UTI examination parameters. Research Methods : The method used is an analytic observational design with cross sectional design using primary data and analyzed with the Spearman rank test. Results : The results showed that in 198 patients with suspected UTI, 123 (62%) were positive for leukocyte esterase, 16 (8.1%) were positive for nitrite. The total number of bacterial countshowed 82 people (41%) with bacteriuria ≥10 5 CFU/mL. Found 61 Gram-negative bacilli and 21 Gram-positive cocci with 21 different bacterial species. Antibiotic sensitivity test showed 51% sensitive, 6% intermediate and 43% resistant. Correlation of leukocyte esterase with nitrites (p 0.023<0.05), total bacteria count (p 0.00<0.05), Gram negative bacilli (p 0.00<0.05), and Gram positive cocci (p 0.533>0.05), antibiotic sensitivity test (p 0.794 >0.05) and bacterial species (p 0.316>0.05). Conclusion : The results showed that there was a correlation between the level of positivity of leukocyte esterase and nitrite, total bacteria count and Gram-negative bacilli, but there was no correlation between Gram-positive cocci, bacterial species and antibiotic sensitivity tests.